Analysis of Students' Understanding of the Carbon Cycle through the GCCDI Approach in Environmental Chemistry Education - Shabrina, Annida Nurul; Nursaadah, Euis (Chemistry Education Department of Education and Teaching Faculty, 2024)
This study aims to analyze the understanding of first and second-year Chemistry Education students about the global carbon cycle. The design of this research is descriptive research, using the Global Carbon Cycle Diagnostic Instrument (GCCDI) instrument with 11 questions. The subjects of this study were first- and second-year undergraduate students of Chemistry Education at Bengkulu University, with a total of 15 students in each group. The students' understanding was analyzed qualitatively through the survey method. The data were analyzed and categorized into four groups: understand, misconception, doubt, and do not understand for the GCCDI. The students' understanding was categorized into simple, medium, and complex schemes for the survey method. The results indicated that, for first- and second-year students, respectively, the category of understanding comprised 53.31% and 58% of responses, the misconception category accounted for 22.38% and 27.24%, the doubtful category represented 4.8% and 6.65%, and the category of